Horizontal mergers in the presence of vertical relationships - Arghya Ghosh; Hodaka Morita; Chengsi Wang (University of Mannheim, Department of Economics, 2014)
We study welfare effects of horizontal mergers under a successive oligopoly model and find that downstream mergers can increase welfare if they reduce input prices. The lower input price shifts some input production from cost- inefficient upstream firms to cost-efficient ones. Also, the lower input price makes upstream entry less attractive, reduces the number of upstream entrants, and decreases their average costs in the presence of fixed entry costs. We identity necessary and sufficient conditions for a reduction in input prices and welfare-improving horizontal mergers under a general demand function. Qualitative nature of our findings remains unchanged for upstream mergers.
urn:nbn:de:bsz:180-madoc-373017
Keywords: L13; L41; L42; 330; merger; successive oligopoly; welfare; reallocation; rationalization